Subsets of CD1c+ DCs: Dendritic Cell Versus Monocyte Lineage - Heger, Lukas; Hofer, Thomas P.; Bigley, Venetia; de Vries, I. Jolanda M.; Dalod, Marc; Dudziak, Diana; Ziegler-Heitbrock, Loems (Frontiers in Immunology, 2020)
Currently three bona fide dendritic cell (DC) types are distinguished in human blood. Herein we focus on type 2 DCs (DC2s) and compare the three defining markers CD1c, CD172, and CD301. When using CD1c to define DC2s, a CD14+ and a CD14− subset can be detected. The CD14+ subset shares features with monocytes, and this includes substantially higher expression levels for CD64, CD115, CD163, and S100A8/9. We review the current knowledge of these CD1c+CD14+ cells as compared to the CD1c+CD14− cells with respect to phenotype, function, transcriptomics, and ontogeny. Here, we discuss informative mutations, which suggest that two populations have different developmental requirements. In addition, we cover subsets of CD11c+CD8− DC2s in the mouse, where CLEC12A+ESAMlow cells, as compared to the CLEC12A−ESAMhigh subset, also express higher levels of monocyte-associated markers CD14, CD3, and CD115. Finally, we summarize, for both man and mouse, the data on lower antigen presentation and higher cytokine production in the monocyte-marker expressing DC2 subset, which demonstrate that the DC2 subsets are also functionally distinct.
CRIS-Team Scopus Importer:2020-10-30
Keywords: CD14; CD172; CD1c; CD301; DC subsets; DC2; dendritic cells